Successful Retrieval of Embolized Amplatzer Septal Occluder from Descending Thoracic Aorta: A Surgical Emergency. - Rahman, CM Mosabber; Alauddin, Md; Vaidya, Satish; Das, Debasish; Bhuiyan, Arif Ulla; Hoque, Md Rezwanul; Rahman, Md Mukhlesur (University Heart Journal, 2019)
Amplatzer septal occluder is widely used by the cardiac interventionists as an effective alternative to traditional surgery for atrial septal defects. However, although rare, device may embolize during or after procedure due to several reasons. We report a case of device embolization into the descending thoracic aorta during percutaneous closure of ASD in a 14-year-old girl which was successfully retrieved by emergency surgery at Department of Cardiac Surgery, University Cardiac Centre, Bangabandhu Sheikh Mujib Medical University, Bangladesh. University Heart Journal Vol. 15, No. 1, Jan 2019; 37-39